Surface modification in inorganic filler of mixed matrix membrane for enhancing the gas separation performance - Rosyadah Ahmad, N.N. (Walter de Gruyter GmbH, 2016)
The development of mixed matrix membrane (MMM) in gas separation process has drawn great attention due to its promising properties. MMM consists of a polymer as the matrix phase, whereas the inorganic filler serves as the dispersed phase. However, poor contact between these two phases often results in unselective gas flow and becomes one of the major issues in the MMM development. Currently, various modification techniques of the inorganic filler to improve the compatibility between the polymers and the particles have been reported. Because of this modification, the CO2 separation from natural gas is expected to enhance. This review provides a better understanding about the modification of inorganic filler. Mechanisms and factors affecting the modification of filler such as the effect of solvent polarity, the effect of water content in solvent, and the effect of drying condition are discussed. The details of the current progress in the MMM involving the silane-modified fillers are also summarized. Â© 2016 by De Gruyter 2016.